Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To determine which ordered pair [tex]\((x, y)\)[/tex] is the solution to the given system of linear equations, we need to solve the system:
[tex]\[ \begin{cases} 3x + 3y = -3 \\ -2x + y = 2 \end{cases} \][/tex]
Let's go through the steps to solve this system:
1. Simplify the First Equation:
The first equation can be simplified by dividing each term by 3:
[tex]\[ x + y = -1 \tag{1} \][/tex]
2. Substitute [tex]\( y \)[/tex] from Equation (1) into the Second Equation:
From Equation (1), we can express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ y = -1 - x \][/tex]
3. Substitute [tex]\( y = -1 - x \)[/tex] into the second equation [tex]\(-2x + y = 2\)[/tex]:
[tex]\[ -2x + (-1 - x) = 2 \][/tex]
Simplify and solve for [tex]\( x \)[/tex]:
[tex]\[ -2x - 1 - x = 2 \][/tex]
[tex]\[ -3x - 1 = 2 \][/tex]
[tex]\[ -3x = 3 \][/tex]
[tex]\[ x = -1 \][/tex]
4. Find [tex]\( y \)[/tex]:
Substitute [tex]\( x = -1 \)[/tex] back into Equation (1):
[tex]\[ y = -1 - (-1) \][/tex]
[tex]\[ y = -1 + 1 \][/tex]
[tex]\[ y = 0 \][/tex]
Thus, the solution to the system of equations is the ordered pair [tex]\((-1, 0)\)[/tex].
Now, let's check which of the given pairs match this solution:
[tex]\[ \begin{aligned} &\text{1. } (-1, 0) \quad \text{Yes, it matches.} \\ &\text{2. } (0, -1) \quad \text{No, does not match.} \\ &\text{3. } (1, -2) \quad \text{No, does not match.} \\ &\text{4. } (1, 4) \quad \text{No, does not match.} \end{aligned} \][/tex]
So, the ordered pair [tex]\((-1, 0)\)[/tex] is indeed the solution to the given system of linear equations. Therefore, the correct answer is [tex]\((-1, 0)\)[/tex], and it corresponds to the first option provided.
[tex]\[ \begin{cases} 3x + 3y = -3 \\ -2x + y = 2 \end{cases} \][/tex]
Let's go through the steps to solve this system:
1. Simplify the First Equation:
The first equation can be simplified by dividing each term by 3:
[tex]\[ x + y = -1 \tag{1} \][/tex]
2. Substitute [tex]\( y \)[/tex] from Equation (1) into the Second Equation:
From Equation (1), we can express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ y = -1 - x \][/tex]
3. Substitute [tex]\( y = -1 - x \)[/tex] into the second equation [tex]\(-2x + y = 2\)[/tex]:
[tex]\[ -2x + (-1 - x) = 2 \][/tex]
Simplify and solve for [tex]\( x \)[/tex]:
[tex]\[ -2x - 1 - x = 2 \][/tex]
[tex]\[ -3x - 1 = 2 \][/tex]
[tex]\[ -3x = 3 \][/tex]
[tex]\[ x = -1 \][/tex]
4. Find [tex]\( y \)[/tex]:
Substitute [tex]\( x = -1 \)[/tex] back into Equation (1):
[tex]\[ y = -1 - (-1) \][/tex]
[tex]\[ y = -1 + 1 \][/tex]
[tex]\[ y = 0 \][/tex]
Thus, the solution to the system of equations is the ordered pair [tex]\((-1, 0)\)[/tex].
Now, let's check which of the given pairs match this solution:
[tex]\[ \begin{aligned} &\text{1. } (-1, 0) \quad \text{Yes, it matches.} \\ &\text{2. } (0, -1) \quad \text{No, does not match.} \\ &\text{3. } (1, -2) \quad \text{No, does not match.} \\ &\text{4. } (1, 4) \quad \text{No, does not match.} \end{aligned} \][/tex]
So, the ordered pair [tex]\((-1, 0)\)[/tex] is indeed the solution to the given system of linear equations. Therefore, the correct answer is [tex]\((-1, 0)\)[/tex], and it corresponds to the first option provided.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.